Program home visit Costa Rica's health system: guidelines for improvement - Solís Cordero, Katherine (2015)
Introduction. Home visit is the main strategy of primary care by bringing health services to the homes and workplaces of people, which allows knowing the needs of the population firsthand. Thus, home visit by the ATAP represents the first contact of the individual, family and community with the health system, with significant benefits both individually and collectively. This research responds to the need to identify the elements that the home visiting program needs to improve modify or replace in order to maximize the provision of this service.Method. It is a qualitative, observational analytic study. Data were collected through documentary research, key informant interviews and focus group. The analysis was performed from the grounded theory.Results. The main results showed the existence of elements at the level of the health system, home visiting program and the figure of the ATAP that should be reviewed, modified or replaced to the home visit, thus it has bigger and better results for the population and the health system.Conclusion. The Home Visiting Program is strength of the Costa Rican health system to address health inequities. However, it is imperative to make decisions and implementation of actions that promote the improvement and increased results of the home visit at a family and community level.